(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Marketing Efficiency of Organic Rice in PT Bali Sri Organik. PT Bali Sri Organik (PT BSO) is a company that has been producing and marketing organic rice since 2012 and has been certified organic by LeSOS, ICERT, and ACT. The company partners with several subaks in the Bali region in developing organic rice. This study aims to examine marketing channels and margins, producer’s share and analyze the marketing efficiency of organic rice from PT BSO. In analyzing marketing efficiency, this research is limited to white and red rice marketing channels in the Bali region. The types of data used in this study include quantitative and qualitative data, while the data sources come from primary and secondary data. Methods of data collection using interviews with key informants and documentation. Data analysis uses qualitative analysis to examine marketing channels and quantitative analysis to analyze marketing margins, producer’s share and marketing efficiency. The results of the study show that there are three marketing channels at PT BSO, namely: channel 1 (producer - final consumer); channel 2 (producer – retailer – final consumer) and channel 3 (producer – wholesaler– retailer – final consumer). In 2022 PT BSO distributes 5,920 kg of rice, channels 2 and 3 are the marketing channels with the largest sales volume, respectively 42% and 51% of total sales. On channel 1 there is no marketing margin because producers sell directly to consumers. The smallest margin for white rice is in channel 3 of Rp. 6,270/kg with a margin percentage of 25.83%, while the smallest margin for red rice is in channel 2 of Rp. 4,967/kg with a margin percentage of 18.89%. The highest producer’s share is in channel 1 of 100% for both types of rice. From the three types of channels, channel 3 is the most efficient marketing channel with a value of 8.81% for white rice and 7% for red rice. In addition, channel 3 has a large sales volume with the lowest marketing costs. Based on this research, it can be suggested to PT BSO to increase sales on channel 3.